Jakob Factory: Tropical Sustainable Architecture - G8A architects; rollimarchini architects (urbanNext, 2021)
The Jakob Factory project offered the design partnership of rollimarchini architekten from Bern and Swiss-born G8A Architects the unique opportunity to propose a highly innovative and highly specific manufacturing space, set to become a design reference for tropical sustainable architecture. The factory houses the specialist steel rope producers Jakob Rope Systems, a high-quality manufacturing organization, specializing in custom-made steel meshing for private and industrial uses. The partnership of organizations applied their pillar value of sustainability, both environmental and social, to all phases of the design process, from conception to execution and projected developments.
Densities, Designing Matter, Energy and sustainability, Formats, g8a architects, Middle Density, Project, Topics
Comfort, Design process, Design strategies, Environmental, Factory, Greenery, Industrial, Innovation, Land management, Living system, Modular Design, Passive design, Passive ventilation, Performative Envelope, Project, Sustainable, Vertical greenery, Vietnam, Working Space
Keywords: Architecture; Sustainability; Ho Chi Minh City, Vietnam; Vietnam